Pinworms (Nematoda: Thelastomatoidea) from Insects Collected in Mississippi, USA, with description of a new species of Protrellus Cobb, 1920 from the Cockroach Ischnoptera deropeltiformis Brunner von Wattenwyl, 1865 (Blattaria: Ectobiidae) - Carreno, Ramon A. (Zootaxa, 2018)
Thelastomatoid nematodes from the hindguts of several species of insects were collected in 4 localities in Mississippi, U.S.A. Protrellus browni n. sp. is described from Ischnoptera deropeltiformis (Blattaria: Ectobiidae) using light and scanning electron microscopy. This species is distinguished on the basis of its large size as well as its large eggs having one broad end tapering toward the opposite pole and with the presence of small spines on part of the shell. Protrellus aurifluus (Chitwood, 1932) Basir, 1956 was found in Parcoblatta fulvescens (Blattaria: Ectobiidae). Four other species of blattarians sampled were negative for pinworms. Additional nematodes recovered from other hosts included Zonothrix columbianus Adamson & Buck 1989 (Thelastomatoidea: Pseudonymidae) from Tropisternus blatchleyi blatchleyi and Tropisternus collaris (Coleoptera: Hydrophilidae), Hystrignathus rigidus Leidy, 1850 and Xyo pseudohystrix Travassos & Kloss, 1958 (Thelastomatoidea: Hystrignathidae) from Odontotaenius disjunctus (Coleoptera: Passalidae). These findings include several new host and geographical records.